2020
DOI: 10.3389/fphar.2020.569551
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity of Herbal Medicine and Its Prevention

Abstract: Herbal medicine (HM) has been widely used to treat diseases for thousands of years and has greatly contributed to the health of human beings. Many new drugs have been developed from HM, such as artemisinin. However, artemisinin has adverse effects, such as renal toxicity. In 1993, a study conducted in Belgium reported for the first time that the root extracts of Aristolochia obliqua S. M. Hwang led to progressive interstitial renal fibrosis. The nephrotoxicity of HM has attracted worldwide attention. More than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 102 publications
(83 reference statements)
0
13
0
Order By: Relevance
“…Herbal medicine involves the use of natural compounds, which have relatively complex active ingredients with varying degrees of side effects [ 31 , 32 , 33 ]. Many herbs which are found to cause nephrotoxicity exert toxic effects by inducing apoptosis in the renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Herbal medicine involves the use of natural compounds, which have relatively complex active ingredients with varying degrees of side effects [ 31 , 32 , 33 ]. Many herbs which are found to cause nephrotoxicity exert toxic effects by inducing apoptosis in the renal tubular cells.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the longterm use of 1.2 g/kg 2036S-QXR is relatively safer. Since the kidney is the most vulnerable to herb plants (Xu et al 2020), it is necessary to take precautions to prevent nephrotoxicity during the long-term administration of 2036S-QXR.…”
Section: Discussionmentioning
confidence: 99%
“…However, the toxicity of herb plants has been underestimated, and there is inadequate information regarding the safety and toxicity risks associated with their use (Charen & Harbord 2020;Liu et al 2020). It has been reported that herb plants may cause adverse effects, such as hepatotoxicity and nephrotoxicity when consumed repeatedly over a long period (van Quan et al 2020;Xu et al 2020). Thus, it is necessary to evaluate the toxicity profile of herb plants to provide recommendations regarding their safe use.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lastly, certain herbs have potentially toxic effects on the liver and kidneys. For instance, berberine and coumarin have potential hepatotoxicity, and β-escin and aristolochic acid may cause nephrotoxicity [ 121 ]. Standardized and comprehensive toxicity studies will be necessary to verify the safety of the compounds for clinical application.…”
Section: Clinical Translation and Its Challengesmentioning
confidence: 99%